OPPORTUNITIES TO INCREASE COMPETITIVENESS OF COMPANIES THROUGH HUMAN CAPITAL DEVELOPMENT (American Journal of Pedagogical and Educational Research, 2025)
This article analyzed concepts related to "human capital", its origin, actuality and content. This research analyzed the use of comparative analysis, integration, analysis and synthesis. In addition the author gave suggestion over concept of using criteria related to human capital, depending on the state, society and business entities, and gave conclusion concerning direct link among concepts related to human capital.